Genetické príciny vzniku karcinomů stítné zlázy - Jindrichová, S; Vlcek, P; Bendlová, B (Casopis lekaru ceskych, 2004)
Thyroid carcinomas represent only 1% of all human malignancies, but more than 90% of endocrine tumors. It can be histologically divided into papillary, follicular, anaplastic or medullary thyroid carcinomas. Here we report the genetic causes of the development of these tumors. For papillary thyroid carcinoma formation of fused genes of tyrosine kinases (RET proto-oncogene, NTRK1 proto-oncogene and met proto-oncogene) with other genes is typical. They can activate these kinases and induce mutation in BRAF gene. The presence of PAX8/PPARgamma fused gene and ras mutations are important in the development of follicular thyroid carcinoma. Anaplastic thyroid carcinoma derives from the dedifferentiation of papillary and follicular carcinomas as a consequence of mutation or loss of heterozygozity in p53 gene. Medullary thyroid carcinoma comes from parafollicular C-cells, where point somatic and germ-line mutations (in familial form of medullary thyroid carcinoma or in multiple endocrine neoplasia type 2) in the RET proto-oncogene determine its development. Identification of these specific genetic alternations for each type of carcinoma can contribute to precision of the diagnosis, explanation of the origin of carcinomas, establishment of prognosis of the disease or in future as a tool for the target gene therapy.
Keywords: karcinom; Proto-Oncogenes; Proto-Oncogene Mas; protoonkogeny; Mutation; Thyroid Neoplasms; Carcinoma; protoonkogen Mas; zvířata; lidé; protoonkogenní proteiny B-Raf; Humans; Proto-Oncogene Proteins B-raf; mutace; nádory štítné žlázy; Animals